Education 5.0: Future Education Trends in the Smart Society Era - Đặng Ngọc Trung; Bùi Văn Hồng (Journal of Technical Education Science, 2025)
Society 5.0 is a concept that emerged to respond to the disruptions caused by the fourth industrial revolution such as unstable, unpredictable, complex environments and the risk of human dependence on technology. Society 5.0 aims to be human-centered, and driven by technology. Education is one of the most important pillars of each country’s development. The education system in Society 5.0 must develop creative skills, critical thinking, collaboration, communication, and life skills. At the same time, students must have skills, technological knowledge, learning, and innovation skills as well as life and career skills; In addition, learning models in the era of Society 5.0 emphasize students’ ability to seek knowledge, and information from many different sources, build problems, think analytically and cooperate and collaborate in problem-solving. This study aimed to identify issues related to education 5.0 to meet the requirements of society 5.0, thereby proposing approaches to education 5.0. Through the analysis and evaluation of documents, the research results have identified perspectives on Education 5.0. These skills need to be developed in Education 5.0, principles of education 5.0, and proposed approaches to education 5.0. With this result, we expect it to contribute significantly to aiming at and perfecting Vietnam’s educational goals in the 5.0 era and towards the goal of developing human resources in the era of technology and international integration.